Claudin proteins, outside-in signaling, and carcinogenesis - Singh, Amar B. (Pflugers Arch, 2016)
Environment affects an individual’s development and disease risk which then suggest that the environmental cues must have ways of reaching to the cellular nuclei to orchestrate desired genetic changes. Polarized and differentiated epithelial cells join together by cell-cell adhesions to create a protective sheet which separates body’s internal milieu from its environment, albeit in highly regulated manner. Among these cell-cell adhesions, a key role of tight junction, the apical cell-cell adhesion, in maintaining epithelial cell polarity and differentiation is well recognized. Moreover, significant changes in expression and cellular distribution of claudin proteins, integral component of the tight junction, characterize pathophysiological changes including neoplastic growth and progression. Studies have further confirmed existence of complex claudin-based interactomes and demonstrated that changes in such protein partnering can influence barrier integrity and communication between a cell and its environment to produce undesired outcome. Cell signaling is the process by which cells respond to their environment to make dynamic decisions to live, grow and proliferate, or die. Thus, pivotal role of the deregulated tight junction structure/function in influencing cellular signaling cascades to alter cellular pheno-type can be envisaged, however, is not well understood. Needless to mention that advanced knowledge in this area can help improve therapeutic considerations and preventive measures. Here, we discuss potential role of the tight junction in the regulation of Boutside-in^ signaling to regulate cancer growth, with specific focus upon the claudin family of proteins.